2021
DOI: 10.11591/eei.v10i5.3109
|View full text |Cite
|
Sign up to set email alerts
|

Experience moderator effect on the variables that influence intention to use mobile learning

Abstract: The study has two objectives, first is exploring the variables that affect the intention to use mobile learning and second is investigating the experience moderator effect on the variables that influence intention to use mobile learning in higher education institutions (HEI) in Iraq. Then formulate a model for intention to use mobile learning. A questionnaire has been conducted in this research for collecting the feedback from the participants. The findings confirmed that social influence (SI), performance exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…This indicates that if the HEI in Iraq aims to enhance the usage of ML, they have to pay attention to PE, EE, SI, and FC. These findings are consistent with prior literature such as [21]- [23] which referred to the importance of PE, EE, SI, and FC in the usage of technology. The findings also showed that satisfaction which is part of the ISSM is also an important factor.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This indicates that if the HEI in Iraq aims to enhance the usage of ML, they have to pay attention to PE, EE, SI, and FC. These findings are consistent with prior literature such as [21]- [23] which referred to the importance of PE, EE, SI, and FC in the usage of technology. The findings also showed that satisfaction which is part of the ISSM is also an important factor.…”
Section: Discussionsupporting
confidence: 93%
“…Since this study is examining the student, the study focuses on explaining the role of factors that include gender and experience as a moderating variables while other moderators such as age and education were not included due to the similarities among users in terms of age and education [9]. Along with the variables of UTAUT, additional variables were included to account for the context of this study, and these include the self-efficacy, enjoyment, and innovativeness [21]- [23]. In addition, from information system success model (ISSM), the variables satisfaction and quality of service were added.…”
Section: Theoritical Frameworkmentioning
confidence: 99%
“…The word intention refers to the subjective possibility of people taking specific actions. Intention to use is considered a behavior that emphasizes the intention to use and positively affects the actual user; therefore, intention to use has a positive relationship with the user (Izkair & Lakulu, 2021). Successful system adoption is greatly influenced by a person's attitude toward utilizing new technology and systems (Yoon et al, 2020).…”
Section: Technology Acceptance Model (Tam)mentioning
confidence: 99%
“…Sustainble education can be delivered in a developing country like Bangladesh by ensuring these facilities [25]. According to Izkair and Lakulu [26] discovered that only five factors are influencing intention to use mobile learning in higher education institutions (HEI), the factors are "facilitating conditions", "performance expectancy", "effort expectancy", "social influence", and "satisfaction". According to Mahareek et al [27], students in higher education institutions can study more effectively by combining machine learning algorithms with educational data.…”
Section: Litreture Reviewmentioning
confidence: 99%